THE ASSESSMENT OF EFFICACY AND OF SAFETY USING SELF-MONITORING OF DISEASE ACTIVITY VIA INTERNET PORTAL IN THE MANAGEMENT OF PATIENTS WITH RHEUMATOID ARTHRITIS - G. G. Bagirova; E. V. Lygina; S. S. Yakushin; M. I. Kozminskaya (Архивъ внутренней медицины)
Objectives: Maximally quickly identify the exacerbation of the disease and timely strengthen the therapy, for more rapid achievement of remission or low disease activity.Methods: The authors created an interactive web portal for self-monitoring of RA activity. The patient management model using this method is that a patient conducts a monthly self-evaluation of the disease activity and transmits this information to his treating doctor in a remote manner via the web portal. In case of worsening and in the absence of any dynamics, according to the patient, he was invited to the center, where this information was verified by a doctor. If, in the patient’s opinion, there was an improvement, he did not come to clinic, but continued therapy. Currently, 30 women with RA, age 57 (38; 71), who completed the 6-month treatment period, are included in the study. 20 women included in the control group, average age 60.5(40; 77).Results: During 6 months, there was a positive dynamic of the course of the disease, the activity of the RA by DAS 28 decreased. Initially, 5 patients (16.7%) had high DAS activity, 24 — moderate (80%), 1low (3.3%). After 6 months of treatment 8 patients (26.7%) had low activity, 22 (73.3%) achieved remission. The mean value of the DAS 28 index at the time of inclusion was 3.99 (2.46; 5.78) and after 6 months of management 2.175 (0.79; 4.31), a statistically significant decrease (Wilcoxon T-test = 5). The DAS 28 index at the time of control group was 4,1 (2.46; 5.78) and after 6 months of management 3,9 (0.79; 4.31), a statistically significant decrease (Wilcoxon T-test = 5). Analysis of clinical and laboratory parameters did not reveal statistically significant deviations.Conclusions: The 6-month period of patient management via the Internet portal for self-monitoring of rheumatoid arthritis activity proved the possibility of achieving remission and low disease activity in all patients.